2015
DOI: 10.1039/c5ra18727c
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of sparger configuration on the hydrodynamics of a full-scale membrane bioreactor using computational fluid dynamics

Abstract: A three-phase computational fluid dynamics (CFD) simulation was carried out in a full-scale membrane bioreactor to investigate the effect of sparger configuration on various hydrodynamic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The other was for the whole membrane module, such as applying the plug flow model to investigate the plate, , tubular, and spiral wound membrane modules, the single-stage or multi-stage CSTR model to investigate hollow fiber membrane modules, , and some special membrane modules , to investigate the removal and residence of filtrate. Especially, Amini et al studied RTD in a full-size biomembrane reactor and found that the system was closer to plug flow conditions when the flow rate at the inlet was large, the liquid viscosity was low, and the gas inlet was at the bottom inlet. Xie et al found that the dead zone and effective mixing zone in the device were independent of the rotating speed and flow rate in a laminar state but only related to the rotating speed in a turbulent state in a rotating disk filtration module.…”
Section: Introductionmentioning
confidence: 99%
“…The other was for the whole membrane module, such as applying the plug flow model to investigate the plate, , tubular, and spiral wound membrane modules, the single-stage or multi-stage CSTR model to investigate hollow fiber membrane modules, , and some special membrane modules , to investigate the removal and residence of filtrate. Especially, Amini et al studied RTD in a full-size biomembrane reactor and found that the system was closer to plug flow conditions when the flow rate at the inlet was large, the liquid viscosity was low, and the gas inlet was at the bottom inlet. Xie et al found that the dead zone and effective mixing zone in the device were independent of the rotating speed and flow rate in a laminar state but only related to the rotating speed in a turbulent state in a rotating disk filtration module.…”
Section: Introductionmentioning
confidence: 99%